Phenotypic variation and identification of Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) in China - Zhao, Jing; Watson, Gillian W.; Sun, Yang; Tan, Yongan; Xiao, Liubin; Bai, Lixin (Zootaxa, 2014)
Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) is an invasive mealybug that seriously damages cotton and other important crops. In previous studies in China, the presence of two submedian longitudinal lines of pigmented spots on the dorsum of adult females frequently has been used to identify this species. However, the present study records the occasional absence of pigmented spots in a sample from Guangxi province, China. Specimens without pigmented spots showed all the molecular and morphological characters that separate P. solenopsis from the similar species P. solani Ferris, especially the distribution of multilocular disc pores. In different geographic populations of P. solenopsis in China, mitochondrial COI and nuclear 28SrDNA genes are very similar (99.8–100%), indicating that they are conspecific. For COI, the genetic distance between P. solenopsis and P. solani is more than 3%. A map of the distribution of P. solenopsis in China is given. To help identify both pigmented and non-pigmented P. solenopsis accurately, an identification key to the 16 species of Phenacoccus found in China is provided. The key also identifies five potentially invasive Phenacoccus species not yet established in China, in case they get introduced there.